نظام التفویض الإداري و تطبیقاته في الإدارة الجزائرية - فرجاوي یحي; خضراوي يوسف (جامعة المسيلة, 2025)
As the state evolved from a "watchman state" into an "interventionist state," its functions and responsibilities expanded considerably. This shift led to the emergence of what is known as the system of administrative delegation, introduced to facilitate the smooth operation of the state's administrative functions. The delegation of administrative authority is viewed as a mechanism to mitigate strict centralization, allowing a superior official to transfer part of their competences to a subordinate. The implementation of this system, however, is conditional upon the existence of a legal framework that explicitly permits it, and it must be regulated by specific legal provisions that distinguish it from other comparable administrative systems. Algeria serves as an example of a country that has adopted this dual-path organizational approach, applying it in various forms across its public administrations and institutions.
Keywords: Administrative Delegation; Delegation of Signature; Delegation of Authority; Centralization; Decentralization.